Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/acel.12074
|View full text |Cite
|
Sign up to set email alerts
|

Reduced amyloid‐β degradation in early Alzheimer's disease but not in the APPswePS1dE9 and 3xTg‐AD mouse models

Abstract: SummaryAlzheimer's disease (AD) is hallmarked by amyloid-b (Ab) peptides accumulation and aggregation in extracellular plaques, preceded by intracellular accumulation. We examined whether intracellular Ab can be cleared by cytosolic peptidases and whether this capacity is affected during progression of sporadic AD (sAD) in humans and in the commonly used APPswePS1dE9 and 3xTg-AD mouse models. A quenched Ab peptide that becomes fluorescent upon degradation was used to screen for Ab-degrading cytoplasmic peptida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 50 publications
(70 reference statements)
1
27
0
Order By: Relevance
“…These included descriptions of strain variation in processing of amyloid-beta [34], altered phenotype expression by strain [3537], variations in behavioral testing by strain [38,39], species similarities [40] or differences in molecular signatures of the aging synapse [41], or aging brain [42,43], gender differences in amyloid plaque development within model [43,44] and differences in amyloid-beta degradation and toxicity between mice, humans and large animal models [45,46]. This type of normative data profoundly impacts study design and interpretation, and contributes to the species barrier [18].…”
Section: Resultsmentioning
confidence: 99%
“…These included descriptions of strain variation in processing of amyloid-beta [34], altered phenotype expression by strain [3537], variations in behavioral testing by strain [38,39], species similarities [40] or differences in molecular signatures of the aging synapse [41], or aging brain [42,43], gender differences in amyloid plaque development within model [43,44] and differences in amyloid-beta degradation and toxicity between mice, humans and large animal models [45,46]. This type of normative data profoundly impacts study design and interpretation, and contributes to the species barrier [18].…”
Section: Resultsmentioning
confidence: 99%
“…Immunohistochemistry studies have shown that striatal plaques are predominantly, or entirely, composed of Aβ1–42 and Aβ1–43 [31] , [34] . Familial forms of AD and DS share overproduction of amyloid as the proposed mechanism of amyloid deposition [37] , whereas decreased clearance might be more significant in sporadic AD [38] . Therefore, it might be that the cellular milieu of the striatum is particularly vulnerable to early amyloid accumulation under the conditions of overproduction.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of IDE in the brain decreases with age and during early stages of AD. Overexpression of IDE in transgenic mice can prevent amyloid plaque formation [40]. Inhibition of IDE is identified as one of the crosstalk between T2D and AD [21].…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%